Comet C/2011 J2 (LINEAR) nucleus splitting: Dynamical and structural analysis. (July 2016) - Manzini, Federico; Oldani, Virginio; Hirabayashi, Masatoshi; Behrend, Raoul; Crippa, Roberto; Ochner, Paolo; Pina, José Pablo Navarro; Haver, Roberto; Baransky, Alexander; Bryssinck, Eric; Dan, Andras; De Queiroz, Josè; et al.
Abstract: After the discovery of the breakup event of comet C/2011 J2 in August 2014, we followed the primary body and the main fragment B for about 120 days in the context of a wide international collaboration. From the analysis of all published magnitude estimates we calculated the comet׳s absolute magnitude H =10.4, and its photometric index n =1.7. We also calculated a water production of only 110 kg/s at the perihelion. These values are typical of a low-activity, long-period or new comet. Analysis of the motion of fragment B over the observation period showed that the first breakout event likely occurred between 12 July and 30 July 2014. Nucleus B remained persistently visible throughout the 4-month observation period. The projected separation velocity of nucleus B from the parent body was 4.22 m/s at the time of the breakup and 12.7 m/s at the end of the observation period, suggesting that nucleus B was subjected to a constant deceleration a = 6.87 ∙ 10 − 7 m / s 2 . The spin period of the main nucleus was estimated as 4.56 h±0.05 h by photometric analysis. The structural analysis of the comet showed a cohesive strength of the nucleus greater than ~0.9 kPa; assuming a bulk density of 500 kg/m 3, with a rotation period of 4.56 h the cometary nucleus might have failed structurally, especially if the body was elongated. These results suggest that the nucleus of comet C/2011 J2 has an elongated shape, with a ratio of the semi-minor axis to the semi-major axis β < 0.675 ; the semi-major axis of the pristine nucleus could be larger than 8 km. From this study, we propose that rotational disruption, possibly combined with sublimation pressure, was a reasonable explanation for the breakup event in comet C/2011 J2. Highlights: Discovery of the breakup of the comet C/2011 J2. Determination of the cometary values H and n and of the water production. Measure of the separation velocity of nucleus B from the primary nucleus and of its deceleration. Detection by means of photometry of the main nucleus rotation period. Development of a rotational model of comet C/2011 J2 and effective radius of the nucleus determined.